2016
DOI: 10.1371/journal.pone.0157495
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Inclusive and Evidence-Based Definition of the Maternal Mortality Ratio: An Analysis of the Distribution of Time after Delivery of Maternal Deaths in Mexico, 2010-2013

Abstract: Progress towards the Millennium Development Goal No. 5 was measured by an indicator that excluded women who died due to pregnancy and childbirth after 42 days from the date of delivery. These women suffered from what are defined as late deaths and sequelae-related deaths (O96 and O97 respectively, according to the International Classification of Diseases, 10th revision). Such deaths end up not being part of the numerator in the calculation of the Maternal Mortality Ratio (MMR), the indicator that governments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Maternal mortality surveillance studies such as confidential enquiry have showed that late maternal death is non-trivial in even low-resource settings34,59 and can account for up to 40% of maternal deaths in high-income settings 60. A contemporary linkage study in Mexico found that 18% of maternal deaths are missed when the definition is truncated at 42 days’ post partum 61. As immediate mortality continues to decrease as a result of improved antenatal, obstetric, and post-partum care, it is therefore increasingly likely that the proportion of late maternal deaths will continue to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal mortality surveillance studies such as confidential enquiry have showed that late maternal death is non-trivial in even low-resource settings34,59 and can account for up to 40% of maternal deaths in high-income settings 60. A contemporary linkage study in Mexico found that 18% of maternal deaths are missed when the definition is truncated at 42 days’ post partum 61. As immediate mortality continues to decrease as a result of improved antenatal, obstetric, and post-partum care, it is therefore increasingly likely that the proportion of late maternal deaths will continue to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous studies, we calculated the annual municipal MM ratio and according to place of residence. Estimates were obtained by dividing the number of women (between ages 10 and 49) without social security coverage who died as a result of gestation by the number of live births.…”
Section: Methodsmentioning
confidence: 99%
“…Following previous studies, 23,33 we calculated the annual municipal MM ratio and according to place of residence.…”
Section: Analytical Variablesmentioning
confidence: 99%
“…As reflected in CONEVAL reports, poverty and inequality prevail in Mexico. In 2014, 46.2% of the Mexican population was in poverty and 9.5% in extreme poverty, states such as Chiapas, Estado de Mexico, Veracruz, Guerrero, Oaxaca and Puebla represent around 60% of the population in poverty and extreme poverty [ 8 ]. There is a direct correlation between MMR and poverty indicators.…”
Section: Resultsmentioning
confidence: 99%
“…The programs implemented to date in Mexico have had positive effects but have not been sufficient to reduce maternal mortality, especially if the indicators of maternal mortality in vulnerable population are analyzed. In Mexico, 46.2% of its population live in poverty and 9.5% in extreme poverty, a component that defines this poverty level is the lack of access to health services [ 8 ]. This population is the one that shows higher levels in maternal mortality indicators, there is currently no program focused on reducing maternal mortality in vulnerable population.…”
Section: Introductionmentioning
confidence: 99%